The relationship between disability and parental status: a register study of the 1968 to 1970 birth cohorts - Fredinah Namatovu; Erling Häggström Lundevaller; Lotta Vikström (BMC, 2021)
Abstract Background Having children is a major life course event yet some disabilities could make it biologically challenging and some others could limit access to necessary socioeconomic resources. To date, there is relatively little data on disability and parental status and our study aimed to investigate this relationship. Methods This longitudinal cohort study was based on register data obtained from all people born in Sweden from 1968 to 1970 (n = 440220). We performed descriptive analyses, graphical plots, logistic regression, and Cox regression analyses. Results Our findings from both logistic regression and Cox regression indicated that individuals that started to receive disability benefits at an early age had reduced chances of having children during the follow-up duration. Men with disabilities were less likely to have children when compared to women with disabilities and to men and women without disabilities. Conclusions We found evidence that disability during early adulthood was associated with reduced chances of having children. Findings support policies and programmes aimed at promoting optimal health during early adulthood, as this would promote continued labour force participation, reduce early use of disability benefits, and possibly improve chances of becoming a parent.